Sociolinguistic Implementation in Qiroah Learning to Enhance Merdeka Belajar's Educational Effectiveness at University - Mokhammad Miftakhul Huda; Muhammad Nidhom Hamami Abicandra; Yessi Yulianti (UIN Syekh Wasil Kediri, Indonesia, 2025)
This study addresses the critical need to enhance the effectiveness of Arabic reading (Qiro'ah) instruction within Indonesia’s Merdeka Belajar (Freedom to Learn) program by integrating sociolinguistic approaches. Previous research has primarily focused on traditional pedagogical methods, overlooking the influence of social and cultural contexts on language comprehension, particularly within the flexible framework of Merdeka Belajar. This research aims to analyze the role of sociolinguistics in Qiro'ah learning at UIN KHAS Jember, with a focus on bridging comprehension gaps among students from diverse linguistic backgrounds. Using a qualitative descriptive approach, data were collected through classroom observations, interviews, focus group discussions, and documentation involving students and lecturers. The findings reveal that applying sociolinguistic strategies—such as contextualizing language use according to social factors like dialect, status, and educational background—significantly improves students’ reading comprehension, cultural sensitivity, and classroom participation. The study concludes that sociolinguistically informed teaching methods align effectively with the Merdeka Belajar program’s goals, promoting an inclusive, adaptive, and socially responsive curriculum for Arabic language education. Penelitian ini menjawab kebutuhan mendesak untuk meningkatkan efektivitas pembelajaran membaca bahasa Arab (Qiro'ah) dalam program Merdeka Belajar dengan mengintegrasikan pendekatan sosiolinguistik. Studi terdahulu umumnya berfokus pada metode pengajaran tradisional tanpa mempertimbangkan pengaruh konteks sosial-budaya terhadap pemahaman bahasa, terutama dalam kerangka fleksibel Merdeka Belajar. Penelitian ini bertujuan menganalisis peran sosiolinguistik dalam pembelajaran Qiro'ah di UIN KHAS Jember, khususnya untuk menjembatani kesenjangan pemahaman mahasiswa dari berbagai latar belakang bahasa. Metode deskriptif kualitatif digunakan dengan pengumpulan data melalui observasi kelas, wawancara, diskusi kelompok terarah, dan dokumentasi yang melibatkan mahasiswa dan dosen. Hasil penelitian menunjukkan bahwa penerapan strategi sosiolinguistik—seperti kontekstualisasi penggunaan bahasa berdasarkan faktor sosial seperti dialek, status, dan latar pendidikan—secara signifikan meningkatkan pemahaman bacaan, kepekaan budaya, serta partisipasi aktif mahasiswa. Disimpulkan bahwa pendekatan pengajaran berbasis sosiolinguistik sejalan dengan tujuan program Merdeka Belajar dalam menciptakan kurikulum bahasa Arab yang inklusif, adaptif, dan responsif terhadap keragaman sosial mahasiswa.